2008
DOI: 10.1002/eji.200737430
|View full text |Cite
|
Sign up to set email alerts
|

B‐Raf‐mediated signaling pathway regulates T cell development

Abstract: The activities of the Raf kinase family proteins control extracellular signal-regulated kinase (ERK) activation in many aspects of cellular responses. However, the relative contributions of individual isozymes to cellular functions including T cell responses are still unclear. In addition to Raf-1, another Raf family kinase, B-Raf, is expressed in murine thymocytes and peripheral T cells, and its activation was induced by TCR stimulation. Here, we investigated the function of B-Raf in development of T cells by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
13
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 44 publications
(76 reference statements)
2
13
0
Order By: Relevance
“…These results suggested that sorafenib should suppress activation of T cells after TCR stimulation. As previous report, MAPK, JNK, and Raf kinases are involved in activation and function of T cells 28, 29, and these kinases can be inhibited by sorafenib. Nevertheless, in this study, we found that at lower doses (1 or 5 µM), sorafenib effectively suppressed induction of Tregs without reducing CD25 expression and at the dose of 5 µM, SMAD and non‐SMAD pathways were down‐regulated significantly.…”
Section: Discussionsupporting
confidence: 72%
“…These results suggested that sorafenib should suppress activation of T cells after TCR stimulation. As previous report, MAPK, JNK, and Raf kinases are involved in activation and function of T cells 28, 29, and these kinases can be inhibited by sorafenib. Nevertheless, in this study, we found that at lower doses (1 or 5 µM), sorafenib effectively suppressed induction of Tregs without reducing CD25 expression and at the dose of 5 µM, SMAD and non‐SMAD pathways were down‐regulated significantly.…”
Section: Discussionsupporting
confidence: 72%
“…In line with this, it was shown that B-Raf is activated by TCR signaling (4,20,21,55), that B-Raf deficiency in T cells results in developmental defects in the mouse (21), and that B-Raf is critical for TCR-mediated ERK activation in T cells from rheumatoid arthritis patients (56). In this study, we show that, upon TCR stimulation, the inhibitory N-terminal 14-3-3 binding site of B-Raf (S365) was dephosphorylated, and B-Raf was hyperphosphorylated, again showing that B-Raf is a downstream-signaling molecule of the TCR.…”
Section: Discussionmentioning
confidence: 56%
“…TCR-induced activation of Raf-1 leads to a transient Erk signal, whereas activation by B-Raf leads to sustained Erk activation in T cells (20,21). Although sustained Erk signaling is crucial for IL-2 production by T cells (20,22,23), it is not understood how TCR triggering leads to B-Raf activation.…”
mentioning
confidence: 99%
“…In cells that are wild-type for BRAF, these inhibitors may paradoxically activate ERK signaling via transactivation of RAF dimers (912). This paradoxical activation depends upon signaling upstream of RAF, as in the case of hyperactivating RAS mutations.…”
Section: Discussionmentioning
confidence: 99%